2014
DOI: 10.1038/sc.2014.195
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autonomic function after acute spinal cord injury using heart rate variability analyses

Abstract: Objectives: Spinal cord injury (SCI) often results in severe dysfunction of the autonomic nervous system. C1-C8 SCI affects the supraspinal control to the heart, T1-T5 SCI affects the spinal sympathetic outflow to the heart, and T6-T12 SCI leaves sympathetic control to the heart intact. Heart rate variability (HRV) analysis can serve as a surrogate measure of autonomic regulation. The aim of this study was to investigate changes in HRV patterns and alterations in patients with acute traumatic SCI. Methods: As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 20 publications
2
45
0
2
Order By: Relevance
“…They also found high-frequency HRV (mostly associated with parasympathetic activity) differences between the paraplegia and the AB groups. Recent research has also found significantly reduced sympathetic activity in adults with tetraplegia, 4 whereas no HRV differences were found between adults with paraplegia (T2-T12) and AB controls in sympathetic activity. 5 The purpose of this report is to extend the research conducted in the area of HRV and SCI by, for instance, investigating the influence of SCI, on cardiovascular function using standard and non-linear HRV measures, as well clarifying the relationship between fatigue and HRV as a function of the neurological lesion level in adults with SCI.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They also found high-frequency HRV (mostly associated with parasympathetic activity) differences between the paraplegia and the AB groups. Recent research has also found significantly reduced sympathetic activity in adults with tetraplegia, 4 whereas no HRV differences were found between adults with paraplegia (T2-T12) and AB controls in sympathetic activity. 5 The purpose of this report is to extend the research conducted in the area of HRV and SCI by, for instance, investigating the influence of SCI, on cardiovascular function using standard and non-linear HRV measures, as well clarifying the relationship between fatigue and HRV as a function of the neurological lesion level in adults with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the frequency domain, low frequency (LF) and high frequency (HF) mostly reflect sympathetic and vagal modulations of HRV, respectively. 4,11 In the time domain, decreased variation is often associated with a shift from sympathovagal balance to sympathetic predominance, whereas in the frequency domain this is often reflected in an increase in the LF/HF ratio. The two frequency components (LF, 0.04-0.15 Hz and HF, 0.15-0.35 Hz), expressed in absolute values (ms 2 ), largely represent the degree of sympathetic and parasympathetic control, respectively.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…4 We reviewed this group of patients regarding respiratory frequency throughout their admission in intensive care unit (ICU). Owing to a new data management system, three patients did not have their respiratory rate stored.…”
mentioning
confidence: 99%